SIZE AND PERCENT OVERLAP OF GOBBLER HOME RANGES AND CORE‐USE AREAS IN CENTRAL MISSISSIPPI - K. David Godwin; George A. Hurst; Bruce D. Leopold (Wildlife Society Bulletin)
Abstract: We monitored 53 radio‐equipped gobblers from 1 June 1988 to 30 September 1990 to determine size, internal structure, and percent overlap of home ranges. Gobbler range size averaged 1,130, 653, and 1,134 ha for spring, summer, and fall‐winter, respectively. Annual home ranges varied from 798 to 3,131 ha and averaged 1,941 ha. Statistical core‐use areas were detected in 99% of all seasonal ranges. Percent home range overlap varied (P < 0.05) among spring (5.5%), summer (9.9%), and fall‐winter (16.9%). No significant relationship was detected between estimated gobbler density and range size. Wildlife managers should consider seasonal variance in gobbler movements and behavior when developing management strategies.